Analisis Buku Ajar “Kalamuna” Pengajaran Bahasa Arab di Pusat Studi Bahasa Asing - Ulfah, Yeniati (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2024)
Analyzing textbooks is very important in order to improve the quality of textbooks. The purpose of the analysis is to determine the needs of users, namely lecturers and students, for the textbook. This research is qualitative, this type of research is classified as library research. The data that researchers obtained was qualitative in the form of texts or readings contained in the "Kalamuna" textbook. The discussion of this research is about suitability to the objectives of language teaching, suitability of the topic situation and context, systematic or coherent presentation of material and analysis of book content. The results of this research are that the textbook "Kalamuna" in terms of content is in accordance with the objectives of language teaching, one of which is speaking skills, the topics discussed in the book are also in accordance with students' daily needs, however, there are several points that need to be improved as well. In the contents of the book, vocabulary and practice questions need to be added. The textbook "Kalamuna" can be used in learning Arabic but there must be improvements from the author.